Efficacy of Phage Therapy in Controlling Rabbit Colibacillosis and Changes in Cecal Microbiota - Zhao, Jian; Liu, Yan; Xiao, Chenwen; He, Shaojie; Yao, Huochun; Bao, Guolian (Frontiers in Microbiology, 2017)
Phage therapy is a valid weapon that we could use to fight against pathogens. Bacteriophages kill bacteria and self-proliferate in the digestive tract. Furthermore, it was assumed that phage therapy could preserve the existing gut microbiota. In this study, forty-five rabbits were equally divided into three groups after they were orally inoculated with pathogenic E. coli to induce gut infection. Each group was treated with bacteriophage ZRP1 (Group P), ciprofloxacin lactate (Group A), or phosphate-buffered solution (PBS) (Group N). Another 15 healthy rabbits composed the control group (Group C). The body weight gain decreased significantly, but the white blood cell count, especially the percentage of large white blood cells, and the serum endotoxin levels increased significantly after infection. The result of microscopic examination of the ileum showed that E. coli ZR1 adhered to villi and caused hemorrhage inside the villi. Group P and Group A rabbits recovered after treatments, and both bacteriophage and antibiotic treatment significantly decreased the eaeA gene concentration in cecal contents. The microbiota in cecal contents changed in infected rabbits that were treated with PBS. The relative abundance of Clostridiales and YS2 decreased but the relative abundance of Enterobacteriales increased significantly. According to the principal components analysis, the microbiota of Group P and Group C rabbits were similar to one another in type and relative abundance but different from those of Group N and Group A rabbits. Moreover, the differences of microbiota between Group N and Group A were clear in the third principal component. The results demonstrated that oral administration of bacteriophage can cure gut infection with minimal impact on the cecal microbiota.